Implementasi Program Guru Asuh dalam Membentuk Karakter Peserta Didik dan Relevansinya dengan Pendidikan Islam - Arifandi, Muhammad Khaeri; Wildan; Efendi, M. Harja (CENDEKIA, 2023)
This study aims to describe the foster teacher program and its implementation in shaping the character of students, describe the obstacles and solutions of foster teachers in shaping the character of students, and examine the relationship between the foster teacher program and Islamic education. This study uses a qualitative approach. Data collection was carried out through interviews, observation, and documentation. The results of this study are first, the foster teacher program in shaping the character of students at SMP Negeri 5 Batukliang is a program that builds teacher-parent relationships for students at school with routine interactions every day and weekly meetings in groups. Second, the implementation of the foster teacher program in shaping the character of students was manifested in the formation of characters developed at SMP Negeri 5 Batukliang namely honesty, discipline, responsibility, religion, and courtesy. Third, the obstacles encountered in running the foster teacher program are the lack of concern for foster teachers in schools, the lack of quick response to guide and find solutions when problems occur with their foster children, the tight schedule of teaching and teaching in other schools, the lack of consistency in making or filling out weekly activity progress reports of foster participants. The solution is that students who often do not go to school are given an individual approach outside of the schedule for implementing the foster teacher program, building intense communication with student guardians including carrying out home visits, and maximum guidance